Acute Vision Loss and Conjunctival Hemorrhage as Telltale Symptoms of PIMS-TS - Houda Nassih PhD; Sara Belghmaidi PhD; Rabiy El Qadiry PhD; Ibtissam Hajji PhD; Aicha Bourrahouat PhD; Abdeljalil Moutaouakil PhD; Imane Ait Sab PhD (Global Pediatric Health, 2022)
There is a global concern about children presenting with inflammatory syndrome with variable clinical features during the ongoing COVID-19 pandemic. This paper reports the first pediatric case of bilateral serous retinal detachment and conjunctival hemorrhage as a revealing pattern of the pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS). Despite the severity of multisystemic involvement, the management with steroids was very successful. Complete remission was obtained within 3 months of acute onset.